INVESTIGATING THE STABILITY OF LONG ONE- DIMENSIONAL WAVES IN A SLOPING RUNOFF (World Science, 2020)
The paper is dedicated to the problem of the influence of waves in shallow-water slope flows on the intensity of soil erosion that has not been considered earlier. The stability of one-dimensional continuous waves on the free surface of the sloping runoff is analyzed, both at constant, and with the variable flow along the way. Attention is drawn towards the unsteady flow process and the shape of the free surface in various planes.